Patient Satisfaction with a Novel Tele-Cystoscopy Model: Expanding Access to Bladder Cancer Surveillance for Rural Patients - Aisha O. Kazeem; William Hasken; Terran Sims; Stephen H. Culp; Tracey L. Krupski; Jennifer M. Lobo (Telemedicine Reports)
Background: Tele-cystoscopy involves trained advanced practice providers performing cystoscopy with real-time interpretation by an urologist. The goal of this externally validated care model is to expand the availability of cystoscopy to underserved rural areas. Herein we report on population demographics and describe the socioeconomic benefits of tele-cystoscopy for bladder cancer surveillance. Methods: Using an IRB-approved protocol, patients were consented for dual, sequential cystoscopy wherein they experienced a standard-of-care cystoscopy along with tele-cystoscopy. Patients completed a questionnaire that contained both subjective and objective health and socioeconomic-related questions as well as a satisfaction survey. Patients were also probed about factors associated with transportation to their cystoscopy appointments including gasoline costs, travel time, and time off work. Using the Distressed Community Index, patients were ascribed an economic resource category ranging from prosperous to distressed. Results: In total, 48 patients with a mean age of 55 completed surveys after completing dual cystoscopies. Thirteen patients (27%) were uninsured and 10 patients (20%) had Medicaid as primary insurance. The tele-cystoscopy clinic saved patients an average of 235 miles and 434 min of travel time. In total, 82% of patients resided in a distressed community indicating fewer economic resources. Satisfaction results showed a mean score of 31.38 (out of 32). Conclusions: Patients were satisfied with tele-cystoscopy, noting increased access to health care and fewer disruptions impacting bladder cancer surveillance. Tele-cystoscopy may be a viable option to expand access and improve adherence to guidelines for bladder cancer surveillance, particularly benefiting patients in rural areas and those of lower socioeconomic status.